Content Area Vocabulary Learning. (May 2014) - Fisher, Douglas; Frey, Nancy
Abstract Students' vocabulary knowledge is a significant predictor of their overall comprehension. The Common Core State Standards are raising the expectations for word learning and there are now 4 distinct standards related to vocabulary as well as expectations in other standards, including content areas. To address these expectations, teachers need to ensure that students are provided time to read widely. In addition, they need to intentionally select words worthy of instruction, model their own word solving strategies, and provide students with opportunities to engage in collaborative conversations in which words are regularly used.